Preparation method of hydrated iron oxide ortho-parahydrogen conversion catalyst

By using ultrasonic dispersion and stirring technology at room temperature, combined with rotary evaporation and high-speed shear stirring, a hydrated iron oxide positive secondary hydrogen conversion catalyst with high specific surface area and wide temperature range is prepared, solving the problem of low activity of existing catalysts in different temperature ranges, and achieving high efficiency and low energy consumption catalyst preparation.

CN119771421AActive Publication Date: 2025-04-08CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410007987.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-07
Filing Date
2024-01-04
Publication Date
2025-04-08
Estimated Expiration
2044-01-04

AI Technical Summary

Technical Problem

The existing hydrated iron oxide positive secondary hydrogen conversion catalyst has low catalytic activity in different temperature ranges, and high temperature hydrothermal preparation methods lead to large grain size, small specific surface area, low preparation efficiency and high energy consumption.

Method used

Using ultrasonic dispersion and stirring at room temperature, alkali liquid is added dropwise to the iron salt aqueous solution to form a suspension, and a hydrated iron oxide positive secondary hydrogen conversion catalyst with high specific surface area and wide temperature range is prepared through rotary evaporation and high speed shear stirring technology.

Benefits of technology

It realizes efficient preparation of catalysts, has low energy consumption, high efficiency, wide temperature range and high activity, and has a large specific surface area of ​​the catalyst, which is suitable for hydrogen liquefaction processes at different temperatures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrated iron oxide ortho-parahydrogen conversion catalyst, which comprises the following steps: (1) under ultrasonic dispersion and stirring conditions, dropwise adding alkali liquor into a ferric salt aqueous solution until the pH value of the system is 8.0-10.5, and standing for 1-5 hours to obtain a first suspension; (2) evaporating the first suspension to remove a certain amount of water to obtain a second suspension; (3) adding the modified metal salt solution into the second turbid liquid under a high-speed dispersion condition, and standing for 1-5 hours to obtain a mixed material; and (4) washing, separating, drying and forming the mixed material to obtain the hydrated iron ortho-parahydrogen conversion catalyst. The hydrated iron oxide ortho-parahydrogen conversion catalyst prepared by the method is small in microscopic particle size, low in synthetic reaction temperature, low in energy consumption, high in preparation efficiency and high in catalytic activity in a wide temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogen energy, and in particular relates to a method for preparing a hydrated iron oxide ortho-parahydrogen conversion catalyst for hydrogen liquefaction. Background Art

[0002] Liquid hydrogen has the advantages of easy storage and high safety factor, making it one of the most important ways of hydrogen storage and transportation.

[0003] At room temperature, hydrogen is composed of 75% orthohydrogen and 25% parahydrogen. When the temperature is lowered, the proportion of orthohydrogen gradually decreases, while the proportion of parahydrogen gradually increases. When liquid hydrogen reaches the standard boiling point, the equilibrium concentration of parahydrogen is 99.8%. In the process of hydrogen liquefaction, since the heat released by the ortho-parahydrogen conversion is greater than the latent heat of vaporization of hydrogen, a large amount of liquid hydrogen will be lost. Therefore, in the liquid hydrogen product, the parahydrogen content is required to be greater than 95%. The spontaneous ortho-parahydrogen conversion process is extremely slow, so in the process of hydrogen liquefaction, a catalyst needs to be added to accelerate the conversion of orthohydrogen to parahydrogen.

[0004] The most commonly used catalyst for the conversion of n-parahydrogen is hydrated iron oxide, but this type of catalyst generally has a higher catalytic activity in the temperature range of 70-80K, while the catalytic conversion efficiency in other temperature ranges is relatively low.

[0005] In order to broaden the catalyst's catalytic conversion activity of ortho-parahydrogen in different temperature ranges, CN202111354244.6 discloses a method for preparing a single-element doped iron oxide ortho-parahydrogen conversion catalyst: adding an appropriate amount of alkali solution to an iron salt solution containing a doping element, hydrothermally treating the mixture, and washing, drying, and crushing the resulting precipitate to obtain a highly active hydrated iron oxide ortho-parahydrogen conversion catalyst in a wide temperature range. The method uses a high-temperature hydrothermal method to prepare doped iron oxide, which has a large grain size, which is not conducive to increasing the specific surface area of ​​the catalyst. At the same time, the high-temperature reaction time used is too long, the preparation efficiency is low, and the energy consumption is too high. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a hydrated iron oxide para-hydrogen conversion catalyst. The hydrated iron oxide para-hydrogen conversion catalyst prepared by the method of the present invention has low synthesis reaction temperature, low energy consumption, high preparation efficiency, and high catalytic activity in a wide temperature range.

[0007] The preparation method of the hydrated iron oxide ortho-parahydrogen conversion catalyst of the present invention comprises the following contents: (1) at room temperature, under ultrasonic dispersion and stirring conditions, adding an alkali solution dropwise to an aqueous solution of an iron salt until the pH value of the system reaches 8.0 to 10.5, and standing for 1 to 5 hours to obtain a first suspension; (2) evaporating the first suspension to remove a certain amount of water to obtain a second suspension; (3) adding the modified metal salt solution to the second suspension under high-speed dispersion conditions, and allowing the mixture to stand for 1 to 5 hours to obtain a mixed material; (4) The mixed material is washed, separated, dried and formed to obtain a hydrated iron para-hydrogen conversion catalyst.

[0008] In the method of the present invention, the iron salt in step (1) is one or more of ferric chloride, ferric nitrate and ferric sulfate; the iron salt aqueous solution is Fe 3+ The calculated concentration is 0.5 to 3 mol / L, preferably 1.0 to 2.5 mol / L.

[0009] In the method of the present invention, the modified metals in step (1) are any two of cobalt, nickel, lanthanum and cerium; the modified metal salts can be nitrates, chlorides and the like, and the concentration of the modified metal salt solution is 0.5 to 5 mol / L, preferably 1 to 4 mol / L, based on metal ions.

[0010] The modified metal salt solutions described in step (1) can be prepared separately or mixed.

[0011] In the method of the present invention, the alkali solution in step (1) is an aqueous solution of sodium hydroxide and / or potassium hydroxide, and the alkali solution is OH — The calculated concentration is 1 to 5 mol / L, preferably 1 to 4.5 mol / L.

[0012] In the method of the present invention, the room temperature in step (1) is 20 to 45°C.

[0013] In the method of the present invention, the ultrasonic dispersion in step (1) is carried out under the following conditions: ultrasonic frequency of 20 to 100 kHz, ultrasonic power of 40 to 1000 W, and ultrasonic temperature of 20 to 45°C.

[0014] In the method of the present invention, the stirring in step (1) includes but is not limited to mechanical stirring, magnetic stirring, shaking table and any other method that is conducive to uniform mixing of materials.

[0015] In the method of the present invention, the evaporation described in step (2) is atmospheric pressure evaporation or negative pressure evaporation, preferably rotary evaporation under negative pressure conditions. The operating conditions are: rotation speed 1 to 200 rpm, vacuum degree 0.05 to 200 Pa, and evaporation temperature 20 to 90° C. Preferably, the rotation speed is 20 to 100 rpm, the vacuum degree is 10 to 100 Pa, and the rotary evaporation temperature is 40 to 75° C.

[0016] In the method of the present invention, the degree of water removal in step (2) is 40% to 80% of the total water content in the iron salt aqueous solution and the alkali solution, preferably 50% to 70%.

[0017] In the method of the present invention, the high-speed dispersion described in step (3) refers to the use of ordinary mechanical stirring, magnetic stirring and shear stirring, as well as other dispersion methods that can fully mix the materials. The rotation speed is not less than 1000 rpm, preferably 1500 to 30000 rpm. It is further preferred to use shear stirring, and the operating condition is that the shear speed reaches 5000 to 20000 rpm. The temperature condition of the operation is 20 to 45°C.

[0018] In the method of the present invention, the washing in step (4) can be performed with water until the pH value of the washing liquid is neutral or nearly neutral.

[0019] In the method of the present invention, the separation in step (4) is a conventional process: the washed suspension is separated into solid and liquid by centrifugation, vacuum filtration or filter press to obtain a solid phase.

[0020] In the method of the present invention, the drying in step (4) is carried out at 100-160° C. for 2-48 hours, preferably at 130-150° C. for 6-24 hours.

[0021] In the method of the present invention, the molding in step (4) is to crush the dried product into particles, and then screen out particles of 30 to 60 mesh.

[0022] The hydrated iron oxide ortho-parahydrogen conversion catalyst prepared by the method of the present invention has the following properties: based on the weight of the catalyst, the modified metal is 0.5% to 15% in terms of oxide, the size of the catalyst particles is 30 to 60 meshes, and the specific surface area is 150 to 250 m 2 / g, the crushing strength is 6-16N / particle, the microscopic particle size of hydrated iron oxide is 2-20nm, and the microscopic particle size of hydrated oxide formed by doping elements is 2-10nm.

[0023] The present invention does not adopt a coprecipitation method when preparing a two-element doped hydrated iron oxide, but first reacts an iron salt solution with an alkali solution to form a suspended mixture, and then after being concentrated by rotary evaporation, the solution to be doped is added to the concentrate, and a reprecipitation reaction occurs with the alkaline substance in the concentrate, and finally a two-element doped hydrated iron oxide is formed. The present invention always uses ultrasonic dispersion during the iron salt and alkali solution feeding process, which can avoid the suspension mixture from aggregating to form larger particles, thereby maintaining a highly dispersed state. The present invention adopts a rotary evaporation concentration method to increase the concentration of the alkaline substance in the above-mentioned suspended mixture, and applying shear stirring can increase the dispersion degree of the concentrate, which is conducive to the good dispersion effect of the element to be doped and the element to be doped, and can increase the specific surface area of ​​the product. The reaction temperature of the present invention is low, the energy consumption is small, the efficiency is high, the specific surface area of ​​the product is large, and the catalytic conversion activity of normal parahydrogen is high in a wide temperature range. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with the embodiments. The size of the nanoparticles of hydrated iron oxide is tested by transmission electron microscope bright field and scanning transmission dark field image mode, the size of the formed particles is measured by standard sieve screening, the crushing strength of the formed particles is measured by a strength meter, the specific surface area is tested by low-temperature nitrogen adsorption method, the specific surface area value is calculated according to the BET method, and the mass content of the doped element is measured by X-ray fluorescence spectrometry (XRF). The parahydrogen content is detected by gas chromatography, and the parahydrogen conversion rate calculation formula at 77K is: conversion rate = (parahydrogen content%-25%) / 25.6%. The parahydrogen conversion rate calculation formula at 40K is: conversion rate = (parahydrogen content%-25%) / 63.7%. The parahydrogen conversion rate calculation formula at 20K is: conversion rate = (parahydrogen content%-25%) / 74.6%. The equilibrium content of parahydrogen at room temperature is 25%. Example 1

[0025] Prepare 3.0 mol / L sodium hydroxide solution, 1.0 mol / L ferric chloride solution, and 0.5 mol / L and 1.0 mol / L lanthanum chloride and cobalt chloride mixed solutions respectively. Add a certain amount of sodium hydroxide solution to the ferric chloride solution under mechanical stirring and ultrasonic dispersion (20 kHz, 100 W) at room temperature (25 ° C) to form a suspension, and let it stand for 2 hours. Then, 50% of the water was evaporated by rotary evaporation at a negative pressure of 100 Pa and 45 ° C to obtain a concentrate. Under high-speed shear conditions of 10,000 rpm, a certain amount of the element solution to be doped was added to the concentrate. After standing for 2 hours, the precipitate was repeatedly washed and filtered with water until the pH value of the washing solution was neutral. Use a blast oven to dry the washings at 135 ° C for 12 hours, and then crush them into 30-60 mesh particles to obtain the final product.

[0026] The test results show that the mass content of lanthanum oxide and cobalt oxide in the product is 6.1% and 2.7%, respectively, the crushing strength is 8-15N / grain, and the specific surface area is 213m 2 / g, the microscopic particle size of hydrated iron oxide is 6.7nm, the microscopic particle sizes of hydrated lanthanum oxide and cobalt oxide are 3.6nm and 3.2nm respectively. The normal and para-hydrogen conversion performance test is shown in Table 1. Example 2

[0027] Prepare 3.5mol / L sodium hydroxide solution, 2.0mol / L ferric chloride solution, and 1.5mol / L and 1.0mol / L lanthanum chloride and nickel chloride mixed solutions respectively. Add a certain amount of sodium hydroxide solution to the ferric chloride solution under mechanical stirring and ultrasonic dispersion (20KHz, 100W) at room temperature (30°C) to form a suspension, and let it stand for 3 hours. Then, 60% of the water was evaporated by rotary evaporation at a negative pressure of 100Pa and 45°C to obtain a concentrate. Under high-speed shearing conditions of 20,000 rpm, a certain amount of the element solution to be doped was added to the concentrate. After standing for 3 hours, the precipitate was repeatedly washed and filtered with water until the pH value of the washing solution was neutral. Use a blast oven to dry the washings at 135°C for 12 hours, and then crush them into 30-60 mesh particles to obtain the final product.

[0028] The test results show that the mass content of lanthanum oxide and nickel oxide in the product is 6.7% and 2.3%, respectively, the crushing strength is 8-17N / grain, and the specific surface area is 224m 2 / g, the microscopic particle size of hydrated iron oxide is 7.2nm, the microscopic particle sizes of hydrated lanthanum oxide and nickel oxide are 2.8nm and 2.9nm respectively. The normal and para hydrogen conversion performance test is shown in Table 1. Example 3

[0029] Prepare 4.5mol / L sodium hydroxide solution, 2.5.0mol / L ferric chloride solution, 1.5mol / L and 1.5mol / L cerium chloride and cobalt chloride mixed solutions to be doped respectively. At room temperature (35°C), mechanical stirring and ultrasonic dispersion (20KHz, 100W) a certain amount of sodium hydroxide solution was added dropwise to the ferric chloride solution to form a suspension, which was allowed to stand for 4 hours. Then, 70% of the water was evaporated by rotary evaporation at a negative pressure of 100Pa and 45°C to obtain a concentrate. Under high-speed shearing conditions of 40,000 rpm, a certain amount of the element solution to be doped was added dropwise to the concentrate. After standing for 4 hours, the precipitate was repeatedly washed and filtered with water until the pH value of the washing solution was neutral. The washings were dried at 135°C for 12 hours in a blast oven, and then crushed into particles of 30 to 60 mesh to obtain the final product.

[0030] The test results show that the mass content of cerium oxide and cobalt oxide in the product is 7.0% and 3.1%, respectively, the crushing strength is 9-18N / grain, and the specific surface area is 220m 2 / g, the microscopic particle size of hydrated iron oxide is 10.4nm, the microscopic particle sizes of hydrated cerium oxide and cobalt oxide are 4.5nm and 3.8nm respectively. The normal-parahydrogen conversion performance test is shown in Table 1. Example 4

[0031] Prepare 4.0mol / L sodium hydroxide solution, 1.0mol / L ferric chloride solution, and 0.5mol / L lanthanum chloride and cobalt chloride mixed solutions respectively. Add a certain amount of sodium hydroxide solution to the ferric chloride solution under mechanical stirring and ultrasonic dispersion (20KHz, 100W) at room temperature (25°C) to form a suspension, and let it stand for 4 hours. Then, 50% of the water was evaporated by rotary evaporation at a negative pressure of 100Pa and 45°C to obtain a concentrate. Under high-speed shearing conditions of 30,000 rpm, a certain amount of the element solution to be doped was added to the concentrate. After standing for 4 hours, the precipitate was repeatedly washed and filtered with water until the pH value of the washing solution was neutral. Use a blast oven to dry the washings at 135°C for 12 hours, and then crush them into 30-60 mesh particles to obtain the final product.

[0032] The test results show that the mass content of lanthanum oxide and cobalt oxide in the product is 6.3% and 2.4%, respectively, the crushing strength is 7-16N / grain, and the specific surface area is 214m 2 / g, the microscopic particle size of hydrated iron oxide is 5.6nm, the microscopic particle sizes of hydrated lanthanum oxide and cobalt oxide are 5.4nm and 4.9nm respectively. The normal and para-hydrogen conversion performance test is shown in Table 1. Comparative Example 1

[0033] The preparation conditions are the same as those in Example 1, except that the two-element doping is changed to a single-element doping, only cobalt is added, and the final cobalt oxide content is kept at 8.8%. The product has a crushing strength of 8-15N / particle and a specific surface area of ​​225m 2 / g. The normal-parahydrogen conversion performance test is shown in Table 1. The test results show that the performance of the single-element doped catalyst is weaker than that of the double-element doped catalyst. Comparative Example 2

[0034] The sample was prepared according to the method steps of Example 1 of CN202111354244.6, except that the same amount of nickel was introduced. After testing, the nickel oxide content of the obtained product was 8.5% and the cobalt oxide content was 8.5%. The crushing strength of the product particles was 5-12N / particle, and the specific surface area was 124m 2 / g. The microscopic particle size of hydrated iron oxide is about 760nm, and the microscopic particle sizes of hydrated lanthanum oxide and cobalt oxide are 50nm and 42nm respectively. The para-hydrogen conversion performance test is shown in Table 1. The para-hydrogen conversion performance test is shown in Table 1. Comparative Example 3

[0035] The preparation conditions are the same as those in Example 1, except that the degree of water removal in step (2) is 90%, and the other conditions remain unchanged. After testing, the mass contents of lanthanum oxide and cobalt oxide in the product are 5.7% and 2.8%, respectively, the crushing strength of the product particles is 5-10N / particle, and the specific surface area is 132m 2 / g, the microscopic particle size of hydrated iron oxide is 6.9nm, and the microscopic particle sizes of hydrated lanthanum oxide and cobalt oxide are 21.5nm and 16.4nm respectively. Due to the high evaporation treatment and excessively high alkali concentration, lanthanum and cobalt salts are prone to form large particle precipitation, which cannot form a relatively uniform precipitation with hydrated iron oxide, resulting in a decrease in the strength and specific surface area of ​​the final product, which is not conducive to the improvement of catalytic performance. The performance test of normal and para-hydrogen conversion is shown in Table 1. Comparative Example 4

[0036] The preparation conditions are the same as those in Example 1, except that the degree of water removal in step (2) is 30%, and the other conditions remain unchanged. After testing, the mass contents of lanthanum oxide and cobalt oxide in the product are 4.7% and 1.3%, respectively, the crushing strength of the product particles is 7-15N / particle, and the specific surface area is 203m 2 / g. Due to the low degree of evaporation treatment and insufficient alkali concentration, lanthanum and cobalt salts cannot be fully precipitated and are lost during washing, resulting in a decrease in the content of lanthanum oxide and cobalt oxide in the final product, which is not conducive to the improvement of catalytic performance. The test of normal and para-hydrogen conversion performance is shown in Table 1. Comparative Example 5

[0037] The preparation conditions were the same as those in Example 1, except that high-speed stirring was not used throughout the process, and only conventional 200 rpm was used instead. After testing, the mass contents of lanthanum oxide and cobalt oxide in the product were 6.5% and 2.4% respectively, the crushing strength of the product particles was 7-15N / particle, and the specific surface area was 185m 2 / g. Without high-speed stirring, larger precipitate particles will be generated, which is not conducive to increasing the specific surface area. The normal and para-hydrogen conversion performance test is shown in Table 1.

[0038] Table 1 Parahydrogen conversion of catalysts at different temperatures (%).

[0039] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 77K 96.9 97.4 96.1 97.8 94.8 90.6 93.0 93.4 94.2 40K 96.8 97.9 96.6 98.4 94.3 91.2 92.7 93.2 93.5 20K 97.0 96.9 96.8 98.1 94.6 90.8 93.2 93.1 93.6 Test conditions: catalyst particle size 30-40 mesh, activation conditions 130℃ vacuum drying for 12 hours, volume space velocity 200min -1 .

Claims

1. A method for preparing a hydrated iron oxide ortho-parahydrogen conversion catalyst, characterized in that The method comprises the following contents: (1) under ultrasonic dispersion and stirring conditions, adding alkaline solution dropwise to an aqueous solution of an iron salt until the pH value of the system reaches 8.0 to 10.5, and standing for 1 to 5 hours to obtain a first suspension; (2) evaporating the first suspension to remove a certain amount of water to obtain a second suspension; (3) adding a modified metal salt solution to the second suspension under high-speed dispersion conditions, and standing for 1 to 5 hours to obtain a mixed material; and (4) washing, separating, drying, and molding the mixed material to obtain a hydrated iron ortho-parahydrogen conversion catalyst.

2. The method according to claim 1, characterized in that: The iron salt in step (1) is one or more of ferric chloride, ferric nitrate and ferric sulfate; the iron salt aqueous solution is Fe 3+ The calculated concentration is 0.5~3mol / L.

3. The method according to claim 1, characterized in that: The modified metals in step (1) are any two of cobalt, nickel, lanthanum and cerium; the concentration of the modified metal salt solution is 0.5 to 5 mol / L in terms of metal ions.

4. The method according to claim 1, characterized in that: In the method of the present invention, the alkali solution in step (1) is an aqueous solution of sodium hydroxide and / or potassium hydroxide, and the alkali solution is OH — The calculated concentration is 1 to 5 mol / L, preferably 1 to 4.5 mol / L.

5. The method according to claim 1, characterized in that: The ultrasonic dispersion in step (1) is carried out under the following conditions: ultrasonic frequency of 20 to 100 kHz, ultrasonic power of 40 to 1000 W, and ultrasonic temperature of 20 to 45°C.

6. The method according to claim 1, characterized in that: The evaporation in step (2) is atmospheric pressure evaporation or negative pressure evaporation; preferably, it is rotary evaporation under negative pressure conditions, and the operating conditions are: rotation speed 1 to 200 rpm, vacuum degree 0.05 to 200 Pa, and evaporation temperature 20 to 90°C.

7. The method according to claim 1, characterized in that: The degree of water removal in step (2) is 40% to 80% of the total water content in the iron salt aqueous solution and the alkali solution, preferably 50% to 70%.

8. The method according to claim 1, characterized in that: The rotation speed of the high-speed dispersion in step (3) is not less than 1000 rpm, preferably 1500 to 30000 rpm.

9. The method according to claim 1, characterized in that: The washing in step (4) can be carried out by washing with water until the pH value of the washing liquid is neutral or nearly neutral.

10. The method according to claim 1, characterized in that: The drying in step (4) is carried out at 100-160° C. for 2-48 hours, preferably at 130-150° C. for 6-24 hours.

11. The method according to claim 1, characterized in that: The molding in step (4) is to crush the dried product into particles, and then screen out particles of 30 to 60 mesh.

12. A hydrated iron oxide ortho-parahydrogen conversion catalyst prepared by the method according to any one of claims 1 to 11, characterized in that The properties are as follows: based on the catalyst weight, the modified metal is 0.5% to 15% in terms of oxide, the catalyst particle size is 30 to 60 meshes, and the specific surface area is 150 to 250 m 2 / g, the crushing strength is 6-16N / particle, the microscopic particle size of hydrated iron oxide is 2-20nm, and the microscopic particle size of hydrated oxide formed by doping elements is 2-10nm.

Citation Information

Patent Citations

  • Palygorskite load nickel base biomass tar oil recapitalization hydrogen manufacturing catalyzer and preparation method thereof

    CN101172232A

  • Cobalt-modified hydrated iron oxide catalyst as well as preparation method and application thereof

    CN113385174A

  • Orthohydrogen and parahydrogen conversion catalyst for liquid hydrogen conversion and preparation method thereof

    CN113797928A

  • Method for production of para-hydrogen, catalyst for its realization and method for production of catalyst

    RU2091294C1

  • Au / Fe2O3 CATALYST MATERIALS, METHOD FOR THE PRODUCTION THEREOF AND THEIR USE

    WO2000009259A2